Bonus Mechanisms, Profitability, and Intangible Assets on Transfer Pricing Decisions in ASEAN 5 - Meiliana Jaunanda; Hellen Allan (Postgraduate Program Merdeka University, 2024)
This study aims to examine the effect of bonus schemes or commonly known as bonus mechanism, the concept of company’s profitability described by Return on Asset (ROA) and company’s intangible assets on transfer pricing decisions conducted by using multiple regression analysis. The sample of this study is consistently consist 56 companies with the observation period from 2019 to 2022 collected from consumer sector companies in the ASEAN-5 region. The results of the study is bonus mechanism and intangible assets positively have a significant influence with transfer pricing intensity. The bonus mechanism is able to motivate decision making related to transfer pricing and the difficulty of measuring the right measurement for intangible assets’ value become a loophole in making the decision of transfer pricing, but there is no influence on profitability described by the Return on Asset (ROA) ratio high profits cause company to pay large tax obligations to also have to be paid as part of the consequences of political costs.DOI: https://doi.org/10.26905/afr.v7i2.12772